Shrunken settlements in west Shropshire: the All Souls 1602 map of Alberbury - Silvester, Robert (Medieval Settlement Research, 2021)
The outstanding collection of late Elizabethan estate surveys held by All Souls College, Oxford, have been utilised by historians, particularly to illustrate the medieval open-field systems of the English Midlands. The college’s map of their estate at Alberbury in western Shropshire from 1602 offers a different perspective, for it shows a significant number of hamlets within the parish, many of which have now been reduced to single farms or gentry houses. Revisiting the assessment of the area laid out in the Victoria County History in 1968, this paper highlights the issues of integrating documentary references into the landscape and also seeks to emphasise the value of early cartography in visualising that landscape. Taking a broader view of Shropshire, this and other seventeenth-century manuscript maps seem to suggest that the shrunken settlements may be more a feature of the more hilly western and southern portions of the county.